Information and Communication Technology in Service-Learning: Some Ethical Issues and Concerns - Marcial, Dave E. (Silliman Journal, 2022)
Information and communication technology (ICT) provides pedagogical benefits in teaching and learning. Likewise, it supports innovative servicelearning (SL) as a teaching pedagogy. However, the use of ICT as a support tool in any pedagogical approach poses some ethical issues. This paper explores some ethical issues in the integration of ICT in SL activities. Specifically, this paper describes the ethical issues in using the Internet as a tool in writing SL reflection. This article also explains the ethical concerns in using the web as a tool in SL evaluation. The study employs a review of related literature and a personal interview among service-learners. The ethical issues discussed in this paper include privacy, authenticity of reflection, technology acceptance, reciprocity, informed consent, administration, and methodological alternative. It is concluded that there is a need to seriously address the ICT ethical issues in SL integration.